A Theory of Planned Behavior approach to developing belief-based communication: day hikers and bear spray in Yellowstone National Park. Issue 6 (2nd November 2019) - Miller, Zachary D.
ABSTRACT: Communicating with visitors to parks and other protected areas is an important strategy for reducing human-wildlife conflict. The Theory of Planned Behavior (TPB) can be used to develop communication strategies that target specific beliefs and increase visitor compliance with desired behaviors. In this study, 647 day hikers participated in a self-administered electronic survey via an iPad with a response rate of 85%. A mixed methods approach was used in analyzing the data. Using a logistic regression, attitude, subjective norm, and perceived behavioral all related to self-reported bear spray behavior of day hikers in Yellowstone National Park, with attitude having the strongest effect. From the logistic regression results, open-ended comments were coded to develop 16 unique belief-based messages using the TPB. Managers of parks and other protected areas where bear spray is recommended when hiking can use these results to frame effective communication strategies.